Exhibitions and the Market for Modern British Art: Independent Art of Today at Agnew's Gallery, 1906. Issue 4 (4th August 2020) - Shaw, Samuel; Pezzini, Barbara
Abstract : A full account of the inception, reception, and cultural economics of Independent Art of To'day, a major show at Agnew's London gallery in 1906, illuminates a crucial – but often overlooked – moment in the story of modern art in Britain. Its analysis nuances our understanding of artistic practice, the art market, and viewers' exposure to and understanding of modern art. The exhibition, which featured work by forty living artists united by their resistance to the Royal Academy and their adoption of a 'modern' aesthetic, was at the time seen by many critics to present a pivotal moment in the history of British art. This essay examines the exhibition's criticism and its financial records to shed new light on current debates surrounding the relationship between economic and symbolic value, on the relationship between critics and dealers, and on the development of modern art and the modern art market in Britain.